Environmental adaptability of Canavalia virosa and Flemingia congesta to sandy ash soil of Merapi Volcano, Java - S S Wardoyo; A Z P B Santoso (Brawijaya University, 2016)
Studies on volcanic ash of Mount Merapi erupted in 2010 are limited to only characterization of mineralogical, physical, chemical, and biological properties of the volcanic ash. In order to speed up rehabilitation of soils affected by the volcanic ash, it is necessary to study the application of suitable plant species, which is called bio-mechanic conservation. The purpose of this study was to test the environmental adaptability of Canavalia virosa and Flemingia congesta in sandy soil covered by volcanic ash of Mount Merapi. This study was carried out using 2x4 Split-plot randomized block design with three replicates. The main plot of the design was plant species (Canavalia virosa and Flemingia congesta), while the sub plot was the dose of organic matter application (0, 20, 40, and 60 t / ha). Soil parameters measured were N-total, P-total, available P, available K, and organic matter contents. Plant parameters measured were plant dry weight and plant height. The results showed no significant differences in soil N, P and K contents of all treatments tested in this study after 9 weeks, except C organic content. Canavalia virosa grew well until 9 weeks, whereas Flemingia congesta started to die a 9 weeks after planting.